2020
DOI: 10.2224/sbp.8648
|View full text |Cite
|
Sign up to set email alerts
|

Community satisfaction, sense of community, and social well-being in China

Abstract: Social well-being in communities has received little research attention, particularly regarding the impact of community satisfaction on social well-being. Thus, we examined the link between community satisfaction and social well-being in the Chinese cultural context, and investigated whether sense of community mediates this relationship. We collected survey data from 572 residents living in various communities in Wuhan, Hubei Province, China, and used regression analysis to test the hypotheses. Results reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 0 publications
2
9
0
Order By: Relevance
“…Responses to this measure were assessed on a 5-point scale, from “strongly disagree” to “strongly agree.” An example of measure items was “I believe that people are kind.” The reliabilities of five dimensions were good (ranging from 0.702 to 0.725), and overall α reliability for the present sample was 0.791. Previous studies had confirmed the validity of social well-being measurement of Chinese version we used ( Miao and Wang, 2009 ; Chen and Yu, 2019 ; Chen et al, 2020 ).…”
Section: Methodssupporting
confidence: 65%
See 2 more Smart Citations
“…Responses to this measure were assessed on a 5-point scale, from “strongly disagree” to “strongly agree.” An example of measure items was “I believe that people are kind.” The reliabilities of five dimensions were good (ranging from 0.702 to 0.725), and overall α reliability for the present sample was 0.791. Previous studies had confirmed the validity of social well-being measurement of Chinese version we used ( Miao and Wang, 2009 ; Chen and Yu, 2019 ; Chen et al, 2020 ).…”
Section: Methodssupporting
confidence: 65%
“…The reliabilities of five dimensions were good (ranging from 0.702 to 0.725), and overall α reliability for the present sample was 0.791. Previous studies had confirmed the validity of social well-being measurement of Chinese version we used (Miao and Wang, 2009;Chen and Yu, 2019;Chen et al, 2020).…”
Section: Social Well-beingsupporting
confidence: 64%
See 1 more Smart Citation
“…In that case, perceived feelings may influence intention, and that intention may further influence behaviour (i.e., prompt a use of services). This connection suggests that having a high level of community satisfaction, probably representing the perceived identification of the community (i.e., older adults’ understanding of, attachment to, and support for the community), as well as their own identification with and sense of belonging to the community (Chen et al, 2020), might be a necessary condition for older adults’ intention to convert their HCBC need into actual use. Greater recognition of the moderating effect of community satisfaction should provide a strong stimulus for changes to social work practices in an effort to improve older adults’ community satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…having a high level of community satisfaction, probably representing the perceived identification of the community (i.e., older adults' understanding of, attachment to, and support for the community), as well as their own identification with and sense of belonging to the community(Chen et al, 2020), might be a necessary condition for older adults' intention to convert their HCBC need into actual use. Greater recognition of the moderating effect of community satisfaction should provide a strong stimulus for changes to social work practices in an effort to improve older adults' community satisfaction.To measure the objective resources of care facilities of older adults, we adopted the accessibility of HCBC services and found a significant interaction between the need for HCBC services and the accessibility of those services in changes in HCBC use.…”
mentioning
confidence: 99%